Evaluasi Keberhasilan Sistem Penjaminan Mutu Pendidikan di BLK Surabaya Menggunakan Information Systems Success Model DeLone & McLean - Khusnul Kharisma Ramadhani; Nur Kholis; Sulanam Sulanam; Arif Mansyuri (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to evaluate the implementation of the education quality assurance system at the Surabaya Job Training Center (BLK) using DeLone and McLean’s Information Systems Success Model (ISSM) as the analytical framework. A qualitative research approach with a case study design was employed. Data were collected through in-depth interviews, participatory observation, and document analysis involving management, instructors, quality staff, and trainees. Thematic analysis was applied to examine six model dimensions: system quality, information quality, service quality, use, user satisfaction, and net benefits. The findings reveal that the quality assurance system at BLK Surabaya has been effective in improving work efficiency, process integration, and learning motivation. System, information, and service quality positively contribute to user satisfaction and organizational benefits. Nonetheless, challenges remain in network infrastructure and limited practice equipment. This study extends the ISSM application in government vocational training institutions and provides practical implications for strengthening digital-based education quality assurance in Indonesia. Keywords: Information Systems Success Model, education quality assurance, vocational training center, vocational education